Fixed Point Results on Multi-Valued Generalized (α,β)-Nonexpansive Mappings in Banach Spaces - Kifayat Ullah; Muhammad Safi Ullah Khan; Manuel de la Sen (Algorithms, 2021)
In this paper, we provide and study the concept of multi-valued generalized <semantics>(α,β)</semantics>-nonexpansive mappings, which is the multi-valued version of the recently developed generalized <semantics>(α,β)</semantics>-nonexpansive mappings. We establish some elementary properties and fixed point existence results for these mappings. Moreover, a multi-valued version of the M-iterative scheme is proposed for approximating fixed points of these mappings in the weak and strong senses. Using an example, we also show that M-iterative scheme converges faster as compared to many other schemes for this class of mappings.